Sharing killed the AVMSD star: the impossibility of European audiovisual media regulation in the era of the sharing economy - Indrek Ibrus; Ulrike Rohn (Internet Policy Review)
The paper focuses on the challenges that the ‘sharing economy’ presents to the updating of the European Union’s (EU) Audiovisual Media Service Directive (AVMSD), part of the broader Digital Single Market (DSM) strategy of the EU. It suggests that the convergence of media markets and the emergence of video-sharing platforms may make the existing regulative tradition obsolete. It demonstrates an emergent need for regulatory convergence – AVMSD to create equal terms for all technical forms of content distribution. It then shows how the operational logic of video-sharing platforms undermines the AVMSD logic aimed at creating demand for professionally produced European content – leading potentially to the liberalisation of the EU audiovisual services market. Lastly, it argues that the DSM strategy combined with sharing-related network effects may facilitate the evolution of the oligopolistic structure in the EU audiovisual market, potentially harmful for cultural diversity.